Policy vs Business: Well-Designed Health-Related Food Policy Should Not Let Industry Marketing Undermine its Intended Effects; Comment on "Understanding Marketing Responses to a Tax on Sugary Drinks: A Qualitative Interview Study in the United Kingdom, 2019" - Laura Cornelsen; Soledad Cuevas (Kerman University of Medical Sciences, 2023)
Health-related food policies, such as taxes on unhealthy food and drink, can act as catalysts for food industry to take action which may or may not align with the policy goal of improving population health. This commentary discusses the framework proposed by Forde et al in analysing the food industry marketing responses to the Soft Drink Industry Levy (SDIL), implemented in the United Kingdom in 2018. We suggest and discuss ways which may help broaden the use of the framework to other relevant policies. This includes widening the framework to cover strategies that may have not come up within the SDIL context but have been studied in other contexts. It would also be important to consider interactions between the strategies and with external factors influencing company decisions. Going forward, comprehensive evaluations of health-related policies should consider likely interactions with industry marketing strategies to fully understand potential impacts.